The Influence Of Ethical Leadership And Perceptions Of Justice On Organizational Commitment With The Mediation Of Organizational Identification - Rika Solihah; Amalia Juliana Monika Intan; Sonny Sanjaya (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research delves into the intricate interplay of ethical leadership, perceptions of justice, organizational identification, and organizational commitment within the context of PT Combiphar, a pharmaceutical company in Bandung. Employing a sample of 90 employees, the study utilized a random sampling technique and applied the SMART PLS analysis to investigate the direct and indirect effects among the variables. The results revealed that ethical leadership significantly influences both organizational identification and commitment, highlighting its crucial role in shaping employee attitudes and behaviors. Conversely, perceptions of justice did not exhibit a statistically significant direct impact on either organizational identification or commitment. Notably, organizational identification demonstrated a significant positive relationship with commitment, emphasizing the importance of cultivating a strong emotional connection to enhance overall commitment. Furthermore, the study uncovered that the impact of ethical leadership on commitment is partially mediated by organizational identification. These findings provide practical insights for organizational leaders at PT Combiphar, suggesting that prioritizing ethical leadership practices and fostering organizational identification can be instrumental in cultivating a more committed and engaged workforce in the pharmaceutical sector.